OVERVIEW OF CLIMBING INJURIES - Natalia Kołdej; Zuzanna Kępczyńska; Wiktor Kubik; Joanna Brzoza; Jan Nowak; Barbara Kujawa; Bartosz Zwoliński; Kacper Sukiennicki; Wirginia Bertman; Katarzyna Szewczyk; Kamil Borysewicz; Klaudia Romejko (International Journal of Innovative Technologies in Social Science, 2025)
Over the past two decades, climbing has become a sport of rising popularity. It encompasses various types of indoor and outdoor disciplines, including lead climbing, bouldering, and speed climbing. A particularly significant increase in interest was observed after introducing this sport at the 2020 Tokyo Olympics. Simultaneously, a greater number of climbing-related traumas have occurred.This review aims to improve our comprehension of injury characteristics and to summarize epidemiology, mechanisms, and prevention of such injuries. Literature evidence demonstrates that the lower and upper extremities were most frequently affected as opposed to the spine and head (Buzzacott, 2019). Fractures, sprains, and strains accounted for the largest share of injuries. Overuse injuries predominantly involve the upper extremities, while acute traumatic injuries are more frequently sustained in the lower extremities (Lutter, 2020).Due to a lack of standard procedures for evaluating climbing performance, further studies should prioritise the standardization of research methods. Furthermore, developing evidence-based preventive strategies and accounting for diverse risk factors for climbing-related injuries, such as eating disorders and neglecting the warm-up, are crucial to enhancing patient care.